Worth the dip? Polar bear predation on swimming flightless greater gnow geese and estimation of energetic efficiency - Matthieu Weiss-Blais; David Bolduc; Madeleine-Zoé Corbeille-Robitaille; Frédéric Dulude-de-Broin; Thierry Grandmont; Frédérique Letourneux; Mathilde Poirier; Denis Sarrazin; Pierre Legagneux (Arctic Science, 2023)
As sea-ice cover is shrinking, polar bears (Ursus maritimus, Phipps 1774) face decreased access to seals, their primary prey, resulting in a greater dependance on terrestrial food sources. Whether polar bears can benefit from these terrestrial food sources however depends on their ability to find and capture prey items without expending more energy than is acquired. Here, we report one of the northernmost observations of polar bear predation on adult birds. The bear used a dive-hunting technique, which consisted of submerging itself, approaching underwater and catching flightless greater snow geese (Anser caerulescens caerulescens) from beneath the surface of a tundra pond. After evaluating energy expenditures during swimming and energy intakes from consuming geese, we estimated that this rarely documented dive-hunting technique could be energetically profitable for a certain range of pursuit duration. This observation highlights the behavioral plasticity that polar bears can deploy to punctually exploit land-based food sources.